Design, development and performance of a low cost three-dimensional metal printer - Rosli, Nor Ana (UTeM, 2018)
3D printing or additive manufacturing (AM) for metallic component is one of the most promising processes that offers freedom to produce an intricate design in a single step. The metal AM process is characterised by high productivity, high energy efficiency, and low raw material cost. A functional metal part can be directly built by using AM process. This increases productivity while enabling reduction in cost and time. The technology is a relatively new and emerging technology. Recently, the growing demand in metal-based material application is utilised in 3D printing. The laser-based system is commonly used for commercial 3D metal printing. However, the price of commercial metal-based 3D printer systems is relatively expensive. Moreover, this drawback has severely restricted the technology access to small and medium industry applications. This study develops a new low-cost 3D metal printing machine by using a wire and arc additive manufacturing process. In other to reduce cost, alternative heat sources were used and a new system utilising an open source was developed. The design and development processes on the hardware and electronic components were described and evaluated. A brief description on basic construction, process, and operations to handle the low-cost 3D metal printer, were presented. This study also presents the total bill for material, connection of electronic parts, and illustration of the experimental setup. Besides that, to test the newly developed machine performance, printed samples were manufactured and tested. In this context, two different heat sources were used, which were the metal inert gas (MIG) welding and plasma arc welding (PAW) process. The experimental setup for both heat sources was described. The sample’s accuracy and structure were examined and compared with the computer aided design (CAD) data. In order to obtain more information about the printed bead geometry, the specimen was cut cross-sectionally and captured by using a scanning electron machine (SEM). As a result, two different findings can be found by using two different heat sources. Nonetheless, the result confirms that the newly developed low-cost 3D metal printer with wire feed AM process is relatively acceptable to produce 3D metal structures.